2017
DOI: 10.18632/oncotarget.15395
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative entecavir for patients with HBV-related hepatocellular carcinoma and low levels of viral DNA: analysis using propensity score matching

Abstract: The safety and efficacy of perioperative antiviral therapy for patients with hepatitis B virus related hepatocellular carcinoma and low serum levels of hepatitis B virus DNA are unknown. This retrospective study compared serum levels of hepatitis B virus DNA, liver function, morbidity, and length of hospital stay between patients who underwent hepatic resection alone and patients who received entecavir therapy before and after resection (n = 44 in each group). Propensity score matching was used to reduce confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…This could be explained by the potential possibility that the African and Caucasian may have certain unknown repair mechanism to avoid the damage caused by deficiency of the GSTM1 gene. It is said that the infection of HBV can easily evolve to liver cirrhosis and finally to HCC [63]. In addition, foodstuffs polluted with aflatoxin B1 (AFB1) are also a threat to livers.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the potential possibility that the African and Caucasian may have certain unknown repair mechanism to avoid the damage caused by deficiency of the GSTM1 gene. It is said that the infection of HBV can easily evolve to liver cirrhosis and finally to HCC [63]. In addition, foodstuffs polluted with aflatoxin B1 (AFB1) are also a threat to livers.…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation was defined as an increase of serum HBV DNA > 1 log or reappearance of HBV DNA in patients with undetectable HBV DNA at baseline in 33 studies, [ 19–21,23–30,32–36,38–43,45–48,50–53,56–58 ] while this definition varied in five studies [ 31,44,49,55,59 ] and was not clearly provided in the remaining three studies. [ 22,37,54 ] A definition of HBV‐related biochemical reactivation was not provided in 18 studies, [ 21–27,30,32–34,37–41,54,59 ] while it varied widely among the remaining 23 studies. [ 19,20,28,29,31,35,36,42–53,55–58 ] Only increases in aminotransferase levels attributed to HBV reactivation by the authors were considered HBV‐related biochemical reactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of HBV reactivation (A, all patients; B, patients without prophylactic HBV therapy; C, patients with prophylactic HBV therapy) and biochemical exacerbation (D) in studies including HBsAg‐positive patients with HCC who underwent surgical resection for HCC (Kubo et al, [ 55 ] Jang et al, [ 19 ] Thia et al, [ 56 ] G. Huang et al, [ 57 ] Lao et al, [ 58 ] Dan et al, [ 53 ] Lee et al, [ 59 ] Sohn et al, [ 21 ] Zhang et al, [ 22 ] Xie et al, [ 23,25 ] Chen et al, [ 24 ] Gong et al, [ 26 ] Yuan et al, [ 27 ] S. Huang et al, [ 28 ] Z. Li et al, [ 29 ] X.‐B. Wang et al, [ 30 ] Xu et al, [ 32 ] C. Li et al, [ 33 ] Z.‐Y.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Studies of large cohorts from China Hong Kong, China Taiwan, and Japan have confirmed that concomitant antiviral therapy with curative treatment reduced the recurrence of HCC. [811] However, there was no consensus about which kind of oral antiviral treatment was the best option in the prevention of HBV related HCC recurrence after curative treatment. Therefore, we conducted this study to investigate the different effects of adefovir dipivoxil (ADV) and telbivudine (LdT) on the prognosis of HBV-related HCC after curative resection.…”
Section: Introductionmentioning
confidence: 99%